Discrimination of fearful and angry emotional voices in sleeping human neonates: a study of the mismatch brain responses - Zhang, Dandan; Liu, Yunzhe; Hou, Xinlin; Sun, Guoyu; Cheng, Yawei; Luo, Yuejia (Frontiers in Behavioral Neuroscience, 2014)
Appropriate processing of human voices with different threat-related emotions is of evolutionarily adaptive value for the survival of individuals. Nevertheless, it is still not clear whether the sensitivity to threat-related information is present at birth. Using an odd-ball paradigm, the current study investigated the neural correlates underlying automatic processing of emotional voices of fear and anger in sleeping neonates. Event-related potential data showed that the fronto-central scalp distribution of the neonatal brain could discriminate fearful voices from angry voices; the mismatch response (MMR) was larger in response to the deviant stimuli of anger, compared with the standard stimuli of fear. Furthermore, this fear–anger MMR discrimination was observed only when neonates were in active sleep state. Although the neonates' sensitivity to threat-related voices is not likely associated with a conceptual understanding of fearful and angry emotions, this special discrimination in early life may provide a foundation for later emotion and social cognition development.